PERSEPSI PEGAWAI TERHADAP LINGKUNGAN KERJA FISIK PADA KANTOR BADAN KEPEGAWAIAN DAERAH KABUPATEN PURWOREJO (STIE Rajawali Purworejo, 2021)
This research aims to find out: (1) What are employees' perceptions of the physical work environment at the Purworejo Regency Regional Civil Service Agency Office, (2) What efforts are being made to improve the physical working environment conditions at the Purworejo Regency Regional Personnel Agency Office. This study used descriptive qualitative method. The sample used was a saturated sample because the number of samples taken in this research were all employees at the Purworejo Regency Regional Personnel Agency Office, totaling 53 people. Data was collected using questionnaire techniques which were measured using a Likert scale. The data analysis technique used was recapitulation of questionnaire results and explanation of the questionnaire results. The research results found that 81.13% of employees in the Purworejo Regency Regional Personnel Agency office felt comfortable and satisfied with the direct physical work environment. And there are still 18.87% who do not feel satisfied and comfortable with the physical working environment at the Purworejo Regency Regional Personnel Agency office. There are 81.57% of employees at the Purworejo Regency Regional Personnel Agency office who feel comfortable and satisfied with the physical work environment that has intermediaries or the general environment. And there are still 18.43% who do not feel satisfied and comfortable with the condition of the physical work environment that has intermediaries or the general environment at the Purworejo Regency Regional Personnel Agency office. Efforts are being made to further improve the condition of the physical work environment, namely by means of redesigning the office, more can identify disturbances in the office environment because it is located on the side of the road, the lighting and lighting facilities in the work space are adequate, the color combination does not disturb employees and the air quality in the office is further improved with adequate ventilation.